Героиня второго плана: роман / Анна Берсенева - Берсенева Анна (Русский характер, 2017)
Экземпляры: (20190123) / Инвентарный номер: 34829 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 51 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6